Strengthening Early Detection of Pregnancy Risk Based on Pudji Rochyati's Scorecard in Lidor Village, Rote Ndao Regency - Yenny Puspitasari; Maryam Sarce Samu selly (CV. AFDIFAL MAJU BERKAH, 2026)
The high maternal mortality rate (MMR) in remote areas of East Nusa Tenggara has prompted the need for early detection of pregnancy risks using the Poedji Rochjati Score Card (KSPR). This study aimed to improve the knowledge and skills of community health workers and pregnant women in Lidor Village, Rote Ndao Regency. Using a quasi-experimental one-group pretest-posttest design through a participatory Extension Service Unit (SAP), the population consisted of 50 community health workers and pregnant women with a purposive sample of 30 participants. Instruments included a 20-item Likert questionnaire, KSPR observation sheets, and simulation evaluations; data analysis used descriptive statistics, manual Wilcoxon signed-rank tests, and thematic analysis. The results showed active participation of 16 community health workers and pregnant women with high enthusiasm in the demonstration of filling out the KSPR and the discussion of risk factors. The conclusion is that the SAP intervention is effective in strengthening community screening and referral preparedness in remote areas, although long-term follow-up is needed.